Digging in real-word electronic database for assessing CDK 4/6 inhibitors adherence in breast cancer patients from Romania - Turcu-Stiolica, Adina; Udristoiu, Ion; Subtirelu, Mihaela-Simona; Gheorman, Victor; Aldea, Madalina; Dumitrescu, Elena Adriana; Volovat, Simona Ruxandra; Median, Dragos Mircea; Lungulescu, Cristian Virgil (Frontiers in Pharmacology, 2024)
It is imperative for patients to respect the prescribed treatments to achieve the anticipated clinical outcomes, including the outpatients receiving oral anti-cancer drugs such as selective cyclin-dependent kinase 4/6 inhibitors (CDK 4/6i). With the introduction of three CDK 4/6i drugs in the Romanian pharmaceutical market in 2018, our study aimed to evaluate medication adherence and the influencing factors among patients undergoing treatment with palbociclib, ribociclib, or abemaciclib for advanced or metastatic breast cancer.Methods: Medication adherence was assessed using the Proportion of Days Covered (PDC) method, and Spearman correlation analysis was conducted to explore the relationships between adherence, age, gender, and follow-up duration.The study enrolled 330 breast cancer patients, with an average follow-up period of 14.6±12.5 months for palbociclib, 10.6±7.1 months for ribociclib, and 8.6±6.4 months for abemaciclib-treated patients. A small proportion of patients demonstrated non-adherence: 12.8% for palbociclib, 14.6% for ribociclib, and 14.7% for abemaciclib. Among patients receiving palbociclib, there was no significant correlation between adherence, age (rho = 0.07, p = 0.35), or gender (rho = -0.144, p = 0.054). However, a significant correlation was found with the duration of follow-up (rho = -0.304, p < 0.0001). Similar results were observed for patients receiving ribociclib or abemaciclib. Most patients received combination therapy with letrozole (46%) and exemestane (13%) for palbociclib, letrozole (48%) and fulvestrant (19%) for ribociclib, and fulvestrant (39%) and letrozole (27%) for abemaciclib, Discussion: High adherence rates were observed among patients treated with CDK 4/6i drugs, with no significant differences noted among the three drugs in this class. However, the collected patient data was limited, lacking information on adverse reactions that could potentially lead to treatment discontinuation, as determined by the oncologist's decision not to prescribe. Consequently, a comprehensive understanding of all factors contributing to the low adherence levels is hindered.